Records of species of the hippolytid genus Lebbeus White, 1847 (Crustacea: Decapoda: Caridea) from hydrothermal vents in the Pacific Ocean, with descriptions of three new species - Komai, Tomoyuki; Tsuchida, Shinji; Segonzac, Michel (Zootaxa, 2012)
Five species of the hippolytid shrimp genus Lebbeus White, 1847 are reported from various deep-water hydrothermal ventsites in the Pacific Ocean: L. laurentae Wicksten, 2010 from the East Pacific Rise 13°N; L. wera Ahyong, 2009 from theBrothers Seamount, Kermadec Ridge, New Zealand; L. pacmanus sp. nov. from the Manus Basin, Bismarck Sea; L.shinkaiae sp. nov. from the Okinawa Trough, Japan; and L. thermophilus sp. nov. from the Manus and Lau basins, south-western Pacific. Lebbeus laurentae is fully redescribed because the original and subsequent descriptions are not totallydetailed. Differentiating characters among the three new species and close allies are discussed. Previous records of Lebbeus species from hydrothermal vents are reviewed.